Automated Trading Bot Design and Implementation for Cryptocurrency Transactions (Journal of Universal Science Research, 2023)
In the contemporary landscape, cryptocurrencies have garnered significant attention, attracting a diverse audience. A common challenge faced by many is the lack of automated solutions for trading and investing activities. To address this challenge, we propose an integrated system designed to automate these processes, continuously monitor the market, and make decisions based on pre-defined criteria. Our development approach has been guided by the Agile XP (Extreme Programming) methodology, which has proven instrumental in facilitating effective teamwork, rapid adaptation to changing requirements, and ultimately achieving our project goals.We constructed the application through the following steps: Collecting requirements, Designing, Building, Testing. For system design, we created the ER diagram and user interface design. In the implementation and testing phase, we provided a detailed explanation of the implementation process and thoroughly tested the site's key functionalities. we employed the Relative Strength Index (RSI), a momentum indicator that assesses the extent of recent price fluctuations, to evaluate instances of excessive buying or selling. When the user provides specific input values, the bot initiates automated actions and later displays the results on the trading platform we leverage, which is Binance in our case.Upon completion of our work, we ran a test on the Binance trading platform to identify areas for improvement. Remarkably, the system has demonstrated its ability to carry out tasks independently in our absence. We emphasize the importance of utilizing data science techniques to conduct a comprehensive analysis of market data, as this is an integral part of improving decision-making processes to achieve maximum benefit.